2012
DOI: 10.1016/j.schres.2012.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Anterior limb of the internal capsule in schizotypal personality disorder: Fiber-tract counting, volume, and anisotropy

Abstract: Mounting evidence suggests that white matter abnormalities and altered subcortical–cortical connectivity may be central to the pathology of schizophrenia (SZ). The anterior limb of the internal capsule (ALIC) is an important thalamo-frontal white-matter tract shown to have volume reductions in SZ and to a lesser degree in schizotypal personality disorder (SPD). While fractional anisotropy (FA) and connectivity abnormalities in the ALIC have been reported in SZ, they have not been examined in SPD. In the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Our group recently examined the integrity of the anterior limb of the internal capsule (ALIC) which carries fibers between the thalamus and frontal lobe in patients with SPD. We found decreased volumes of the mid-ventral portion of the ALIC in SPD patients compared to controls; and, fewer fiber tracts in the dorsal portion of the ALIC terminating in BA10 but not BA45; and fewer dorsal-ALIC fibers correlated with greater severity of SPD symptomatology [73]. …”
Section: Neurobiological Studies: Structural and Neurochemical Findingsmentioning
confidence: 99%
“…Our group recently examined the integrity of the anterior limb of the internal capsule (ALIC) which carries fibers between the thalamus and frontal lobe in patients with SPD. We found decreased volumes of the mid-ventral portion of the ALIC in SPD patients compared to controls; and, fewer fiber tracts in the dorsal portion of the ALIC terminating in BA10 but not BA45; and fewer dorsal-ALIC fibers correlated with greater severity of SPD symptomatology [73]. …”
Section: Neurobiological Studies: Structural and Neurochemical Findingsmentioning
confidence: 99%
“…Based on the notion that serotonin-dependent neurotrophic growth factors affect WM integrity measures (Martinowich and Lu, 2007 ), our own studies previously found FA reductions following ELS in the anterior limb of the internal capsule (ALIC), which lies in key circuitry connecting the temporal and frontal regions of the brain (Cannistraro et al, 2007 ; Zou et al, 2008 ). Although the uncinate fasciculus has featured prominently in studies of childhood maltreatment (Huang et al, 2012 ), and the fornix is closely related to the hippocampus (Kubicki et al, 2005 ), the ALIC shows decreased FA in neurodevelopmental disorders such as schizophrenia (Kubicki et al, 2005 ) and schizotypal personality disorders (Hazlett et al, 2012 ). Decreased FA of the ALIC has also been identified as a plausible link between type II diabetes and major depressive disorder (Zhang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Hypergyria in schizophrenia spectrum deviated gyrification patterns in the bilateral temporoparietal regions corresponding to the altered OFC patterns, which were specific to the schizophrenia group, might reflect disturbed structural connectivity in many nerve bundles, connecting OFC with temporoparietal cortices. Furthermore, results from diffusion tensor imaging 52,53 and functional MRI 54,55 studies have generally suggested frontal disconnectivity and its role in the clinical characteristics (e.g., cognitive deficits) of schizotypal patients. However, although we found no significant correlation between the LGI and illness duration, the first-episode schizophrenia subgroup showed a hypergyrification in broader areas than the chronic schizophrenia subgroup, implicating the potential confounding effects of illness chronicity 25 and long-term medication on gyrification index values.…”
Section: Discussionmentioning
confidence: 99%